2020
DOI: 10.1038/s41467-020-18248-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mucosal immunity by transient microbiota depletion

Abstract: Tissue resident memory CD8+ T cells (Trm) are poised for immediate reactivation at sites of pathogen entry and provide optimal protection of mucosal surfaces. The intestinal tract represents a portal of entry for many infectious agents; however, to date specific strategies to enhance Trm responses at this site are lacking. Here, we present TMDI (Transient Microbiota Depletion-boosted Immunization), an approach that leverages antibiotic treatment to temporarily restrain microbiota-mediated colonization resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 75 publications
(115 reference statements)
2
13
0
Order By: Relevance
“…Consistently, a recent study showed that an oral typhoid vaccine was able to induce antigen-specific CD4 + T RM cells in the human small intestine ( 46 ). Additionally, transient microbiota depletion-boosted immunization in mice has been proposed as a strategy to optimize T RM cell generation upon exposure with vaccine antigens ( 47 ).…”
Section: T Rm Cells In Intestinal Infection Contromentioning
confidence: 99%
“…Consistently, a recent study showed that an oral typhoid vaccine was able to induce antigen-specific CD4 + T RM cells in the human small intestine ( 46 ). Additionally, transient microbiota depletion-boosted immunization in mice has been proposed as a strategy to optimize T RM cell generation upon exposure with vaccine antigens ( 47 ).…”
Section: T Rm Cells In Intestinal Infection Contromentioning
confidence: 99%
“…While targeting specific bacterial competitors (present in the mouse microbiome, absent in the human microbiome) may generate more relevant mouse models to study L. monocytogenes infection, their protective potential when administered as probiotics in humans remains to be studied. Alternatively, transient depletion of mouse microbiota may favour intestinal exposure to engineered L. monocytogenes carrying a highly immunogenic antigen 89 . This approach to boost the immune response may be a useful platform to study vaccination at the intestinal mucosa in humans.…”
Section: Use Of In Vivo Infection Models For Human Health Impactmentioning
confidence: 99%
“…Extracellular ATP derived from intestinal microbiota, activated cells and/or damaged tissue restores TGF-βRII expression and TGF-β responsiveness, resulting in CD8 + T cell CD103 upregulation, KLF2 downregulation, enhanced mitochondrial function and T RM formation ( 125 ). On the other hand, microbiota depletion by antibiotic treatment increases the antigen load following LM infection and promotes CXCR3-directed CD8 + T cell accumulation within the large intestinal lamina propria, resulting in increased mucosal CD8 + T RM accumulation and response ( 126 ).…”
Section: Stage 2: Mechanisms That Encourage Cd8 + T Rm To Settle In Peripheral Tissuesmentioning
confidence: 99%